2017
DOI: 10.1002/pits.21994
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading Comprehension to Learners With Autism Spectrum Disorder: Predictors of Teacher Self‐efficacy and Outcome Expectancy

Abstract: Learners with autism spectrum disorder (ASD) often exhibit difficulty in the area of reading comprehension. Research connecting the learning needs of individuals with ASD, existing effective practices, teacher training, and teacher perceptions of their own ability to teach reading comprehension is scarce. Quantitative survey methodology and hierarchical regression analysis were utilized to investigate teacher preparedness to use effective practices, along with the job‐related factors of experience, administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Additionally, the findings of our study are supported by Accardo et al (2017) who examined the knowledge of effective pedagogical practices for reading comprehension for students with Autism Spectrum Disorders. Accardo et al (2017) found that teachers who had more training in effective practices for working with students with Autism Spectrum Disorders had higher self-efficacy ratings of themselves as effective teachers in the inclusive classroom.…”
Section: Discussion Of Findingssupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, the findings of our study are supported by Accardo et al (2017) who examined the knowledge of effective pedagogical practices for reading comprehension for students with Autism Spectrum Disorders. Accardo et al (2017) found that teachers who had more training in effective practices for working with students with Autism Spectrum Disorders had higher self-efficacy ratings of themselves as effective teachers in the inclusive classroom.…”
Section: Discussion Of Findingssupporting
confidence: 74%
“…Due to a lack of professional development for working with students with Autism Spectrum Disorders, the participants reported they lacked confidence and believed they were ineffective teachers. More recently, Accardo et al (2017) examined knowledge of effective pedagogical practices for reading comprehension for students with Autism Spectrum Disorders and how effective instructional practices affect teacher self-efficacy ratings. The researchers found that teachers who had more training in effective practices for working with students with Autism Spectrum Disorders had higher self-efficacy ratings of themselves as effective teachers in the inclusive classroom.…”
Section: Teachers' Self-efficacymentioning
confidence: 99%
“…This study is an investigation of teacher preparedness to use the existing research-based effective practices. It is part of a larger study of teacher self-efficacy and outcome expectancy teaching comprehension to learners with ASD (Accardo et al, 2017). Self-efficacy, stemming from social cognitive theory (Bandura, 1986(Bandura, , 1997, asserts a connection between an individual's perception of their own ability and their related decision-making processes.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…Research related to this article was conducted by Koning (2016) [7], Accardo (2017) [8], Ely (2018) [9], Rosyida (2018) [10], Walgermo (2018) [11], Leko (2019) [12], who discussed reading learning implemented in various levels of education and related to literacy. Muhson (2009) [6], Fakhriyah (2014) [13], Nafiah (2014) [14], Ali (2019) [15], Markušić (2019) [16], conducted research that discussed the implementation of problem based learning model in various scientific studies.…”
Section: Introductionmentioning
confidence: 99%